Age‐related alterations in the nutritional quality of Arctic grayling (Thymallus arcticus). Issue 11 (17th October 2022) - Ma, Kai; Tong, Guangxiang; Zhao, Cheng; Yin, Jiasheng; Wang, Yumei; Zhang, Yongquan
Abstract : Abstract: The biochemical composition of the muscle in Arctic graylings at three age stages was evaluated and compared. For conventional biochemical composition, there was no significant difference in the crude protein content among the three age stages, but the crude fat content in the 1 year old was significantly lower than that of the others ( P < 0.05). For amino acids composition, there was no significant difference in the content of essential amino acids and delicious amino acids among the three age stages, but the essential amino acid index of the 2 year old was the highest (72.205), indicating that its essential amino acid composition was more suitable for human needs. For fatty acids composition, the content of monounsaturated fatty acids (2.759 mg/g) and polyunsaturated fatty acids (3.422 mg/g) of the 3 year old was significantly higher than that of the others ( P < 0.05), and it also had relatively lowest atherogenicity index (0.419) and thrombogenicity index (0.179) and the highest hypocholesterolemic/hypercholesterolemic fatty acid ratio (2.404), indicating that its fatty acid composition was healthier and more beneficial to the prevention of human cardiovascular and cerebrovascular diseases. For minerals composition, the contents of iron, zinc, and copper increased with age, while the contents of selenium and manganese decreased with age, with the highest selenium content in the 1 year old (1.522 mg/kg). The chromium, arsenic, lead, and cadmium contents were all lower than the Chinese national standard. In conclusion, the nutritional composition of Arctic graylings variated with age and consumers could select suitable Arctic graylings based on their nutritional needs. Practical Application: This work analyzed the nutritional components in the muscle of Arctic graylings at different ages, which can provide an effective reference for consumers when purchasing Arctic graylings.